Recycling Mother Liquor to Synthesize Mesoporous SBA-15 Silica - Jia, Lixia; Song, Mingjuan; Ye, Xiuqun; Gu, Haifang; Zou, Chenglong; Niu, Guoxing; Zhao, Dongyuan (Asian Journal of Chemistry, 2013)
SBA-15, a type of mesoporous silica, was prepared using recycled mother liquor. The results showed that ethanol accumulation in the mother liquor with continuous recycling damages the ordered structure of SBA-15 silica. The open heating of the mother liquor above 95 ºC for 2 h can effectively remove ethanol, reducing the ethanol content to below 5 %. The P123 (pluronic EO20PO70EO20 triblock copolymer) and HCl remain in the mother liquor and can thus be utilized in the next preparation. Such treatment allows the mother liquor to be recycled at least five times. In this way, almost no acid or wastewater is discharged. The structures of the synthesized SBA-15 silicas are as well ordered as those from the fresh liquor except for slightly smaller pores and thicker pore walls. Its environmentally friendly character and cost-effectiveness make this method highly suitable for industrial SBA-15 silica production.